Artistic Thought and Its Influence on Global Tourism Companies: A Systematic Review of the Literature - Jesus Enrique Reyes Acevedo; Segundo Humberto Peña Tejada (Eximia, 2025)
Artistic thinking has emerged as an essential driver of innovation, differentiation, and experience value in the tourism sector, particularly as businesses seek to respond to changing consumer expectations in a creative economy. This study critically explores the influence of artistic thinking on tourism businesses' business strategies, models, and practices. The review synthesizes key themes related to how artistic processes such as creativity, design thinking, aesthetic leadership, and storytelling enhance strategic planning, branding, and customer experience in tourism. The analysis reveals that artistic thinking facilitates immersive engagement, co-creation, and cultural authenticity, which are essential for delivering memorable tourism activities. Furthermore, the integration of artistic approaches into marketing and leadership fosters adaptive organizational values ​​and supports the construction of a place-based identity. However, challenges such as resource constraints, lack of management understanding, and institutional resistance often hinder the full acceptance of artistic practices in the business environment. Methodologically, the review adopts a scoping approach, utilizing thematic analysis of peer-reviewed studies selected through a systematic search of academic databases. The findings contribute to the theoretical discourse on inventive industries and offer applicable insights for tourism entrepreneurs, policymakers, and educators seeking to harness artistic thinking for sustainable and competitive advantage. This review identifies significant gaps in the literature, including a lack of empirical studies on specific regions and limited examination of cross-sector collaborations between artists and tourism businesses. It concludes by calling for future research that explores the long-term business impacts of artistic integration and develops frameworks to support artistic innovation in tourism. Overall, this study affirms the transformative potential of artistic thinking in shaping a tourism sector that is more emotionally resonant, more customarily rich, and more strategically agile.